2016
DOI: 10.1186/s40545-016-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacists as immunizers on influenza vaccination coverage in the community-setting in Nova Scotia, Canada: 2013-2015

Abstract: BackgroundAnnual immunization is the most effective way to prevent influenza and its associated complications. However, optimal immunization rates are not being met in Nova Scotia, Canada. Additional providers, such as pharmacists, may improve access and convenience to receive vaccines. Pharmacists began immunizing patients 5 years of age and older within the publicly funded universal influenza vaccination program during the 2013-2014 influenza season. The objective of this study was to evaluate influenza immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
2
16
0
3
Order By: Relevance
“…Pharmacist services were used by patients from all socio-demographic areas, and especially caregivers, healthcare workers and those of working age [ 38 ]. Previous research from Nova Scotia suggested that the addition of pharmacists as immunizers within the publicly funded influenza program increased overall vaccine coverage in the first two years that included pharmacists as immunizers in addition to universal funding [ 40 , 41 ]. This study was able to look at additional data, including data prior to universal funding, geographic distribution data, as well as an additional year of pharmacists as immunizers.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist services were used by patients from all socio-demographic areas, and especially caregivers, healthcare workers and those of working age [ 38 ]. Previous research from Nova Scotia suggested that the addition of pharmacists as immunizers within the publicly funded influenza program increased overall vaccine coverage in the first two years that included pharmacists as immunizers in addition to universal funding [ 40 , 41 ]. This study was able to look at additional data, including data prior to universal funding, geographic distribution data, as well as an additional year of pharmacists as immunizers.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent Canadian data, not included in this systematic review, support generalizability of these results in the Canadian context, as increased vaccination rates for influenza vaccines were observed with the addition of pharmacists as immunizers. [9][10][11]…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados muestran que el 85% de los encuestados acogieron favorablemente la posibilidad de recibir la vacuna en la farmacia. Los motivos por los que la prefieren a los CAP reflejan algunos de los valores que la farmacia como centro de salud aporta a la comunidad: proximidad y accesibilidad del profesional sanitario que les atiende, y coinciden con los recogidos en los estudios que valoran los beneficios de la vacunación por farmacéuticos [17][18][19][20][21][22][23]24,25].…”
Section: Discussionunclassified
“…Otros países (Canadá, Estados Unidos, Australia, Reino Unido, Irlanda, Suiza, Portugal, Dinamarca, etc.) han seguido las recomendaciones de expertos e instituciones sanitarias en el sentido de ampliar el acceso a la vacunación antigripal en ámbitos no tradicionales en especial las farmacias comunitarias [17][18][19][20][21][22][23].…”
Section: Introductionunclassified